Introduction of BIM Methodology in Structural Engineering Education - A. Z. Sampaio; T. T. Farinha; A. M. Gomes (Technological Innovation in Engineering Research Vol. 4, 2022)
The methodology Building Information Modelling (BIM) has been implemented in all sectors of the construction industry. The structural design is a component of a building project, and as so it is important to understand which aspects of the project can admit changes with the implementation of BIM. In relation to the structural project there is still some resistance, justified by the limited ability of interoperability between the BIM modelling and structural analyses software. The study presents the applicability of BIM on structural projects supporting the development of the required sequential stages: the structural model generation; the analytical model preparation to perform the structural analyses and the reinforcement’s detail. In order to evaluate the interoperability between BIM platforms several available software were used, namely ArchiCAD, Revit and ETABS. This study aims to analyze the level of confidence in transfer data processes. This report points out the main strategy of operating BIM-based tools, the main advantages in the use of the methodology and some of the limitations essentially caused by the inefficient degree of interoperability. The study presents the methodology followed in the elaboration of two projects of real cases. The research aims to contribute to the dissemination of BIM in the structural project.